GIS-based accessibility analysis of urban park green space landscape - Zuo Yiqiu; Ding Xinlei; Wei Yajuan; Wang Wenguo; Wang Mingjing (Scientific Reports)
Abstract As an important part of urban green space, the accessibility of leisure and recreation service radius of urban park green space is an important index to reflect the rationality of urban park spatial layout. This paper takes the park green space in the central urban area of Baotou City as the research object, and analyzes the landscape accessibility of the service radius of urban park green space from multiple dimensions through buffer analysis method, gravity model method, cost weighted distance method, traffic cost method and minimum proximity distance method. The results show that: (1) The spatial distribution of urban park green space in Baotou City is characterized by equalization. Among them, Qingshan District and Kundulun District Park Green Space Park Green Space Service Efficiency is the most prominent, and its spatial accessibility index is significantly better than other urban areas; jiuyuan District and Rare Earth High-tech Zone are at the middle level, basically meeting the daily recreational needs of citizens; the Donghe District needs to be improved in key indicators such as park service radius coverage, and the landscape accessibility service effect is poor. (2) The evaluation and analysis of the service radius coverage level of park green space in Baotou City can basically meet the requirements of residents’ leisure and recreation. From the perspective of the service radius accessibility landscape service efficiency classification, the service coverage areas of grade I (11.98%), grade II (17.48%) and grade III (22.45%) show a step-by-step distribution characteristics, and the cumulative coverage rate of the three-level service area reaches 51.91%. However, the spatial heterogeneity analysis shows that there is a significant gradient difference in the service level between administrative division units, reflecting the plate characteristics of green space resource allocation. The park green space in the central urban area of Baotou City shows high service efficiency, and the service radius coverage is good. More than 53% of the parks are higher than the average level. Most of the public green spaces are located in the 20-minutewalking circle of residents, which can basically meet the leisure needs of the surrounding community residents for shared park green space. The overall layout of the park green space system is scientific and reasonable, but the balance of spatial allocation still needs to be further improved, and there is still room for optimization and improvement in the service efficiency of some areas.